Control interno del inventario y su incidencia en la rentabilidad de la empresa Caivel S.A. año 2021 - Romero Córdova , Carolina Elizabeth (2022)
The main objective of this research was to evaluate the incidence of internal inventory control on the profitability of the company CAIVEL S.A. The methodology used in the project was of a qualitative-quantitative nature of an explanatory, descriptive type in which the inductive, deductive, analytical and synthesis methods were applied, the same ones that allowed generating the assessment of the study problem for the elaboration of the conclusions and research recommendations. The data collection process was carried out through observation techniques, surveys and interviews addressed to the administration and the people involved in the internal control of the inventory, and the application of financial indicators to obtain relevant information regarding the problem. The lack of internal control of the company's inventories by the company's administration was evidenced, as well as the lack of training for the operative personnel in a high percentage, which also requires the adequate use of an internal control manual to establish functions and supervise the stock of merchandise, 75% of the workers are unaware of the organizational structure of the company, making it difficult to comply with institutional objectives, while 71% of those surveyed expressed the need to have an administrator who controls all the internal processes. The company CAIVEL S.A has a profit margin of 8% operating, 2% operating margin and 1.49% net margin in the fiscal period 2021.